Respiratory mechanics and peripheral airway inflammation and dysfunction in asthma. Issue 5 (22nd April 2013) - Shirai, T.; Mori, K.; Mikamo, M.; Shishido, Y.; Akita, T.; Morita, S.; Asada, K.; Fujii, M.; Suda, T.; Chida, K.
Summary Background Clinical application of the forced oscillation technique (FOT) has progressed with the spread of commercially available FOT devices. The correlation between respiratory impedance and spirometry has been reported; however, the association with airway inflammation and pulmonary function, in the lung periphery in particular, is unclear. Objective To assess whether respiratory impedance is associated with peripheral airway inflammation and dysfunction in asthma. Methods Subjects included 78 patients with overall controlled asthma. We measured whole‐breath or within‐breath respiratory system resistance (Rrs) and reactance (Xrs) using a commercially available multi‐frequency FOT device (MostGraph‐01), and assessed the correlation with the fraction of exhaled nitric oxide (FeNO), alveolar nitric oxide concentration (CANO), maximal NO flux in the conductive airways (J'awNO), and the N2 phase III slope of single breath N2 washout (delta N2). Results The differences between inspiratory and expiratory phases of Xrs at 5 Hz (X5), resonant frequency (Fres), and a low‐frequency reactance area (ALX) were significantly correlated with CANO; however, there was no correlation between respiratory impedance and FeNO or J'awNO. The delta N2 values were significantly correlated with whole‐breath, inspiratory, and expiratory Rrs and Xrs, except for R20. Conclusions and Clinical Relevance We conclude that respiratory impedance reflects peripheral airway inflammation and ventilation inhomogeneity.